Policy or office?: The determinants of programmatic change in West European political parties - Zohlnhöfer, Reimut; Bandau, Frank (The European social model under pressure, 2020)
Although it is undisputed in the literature that parties’ policy positions move, it is much less clear what actually moves parties. In our paper, we seek to advance the debate on programmatic change in political parties theoretically as well as empirically. We start out by theoretically discussing the relevance of policy-seeking vs. office-seeking with regard to the programmatic positions of parties. This allows us to develop hypotheses regarding the timing and direction of programmatic change. We then move on to test these hypotheses empirically. We present results from comparative case studies of the two most important parties in four West European countries (Germany, Netherlands, Sweden, United Kingdom), which are characterized by dramatically different party systems. We show that in most cases considerations regarding office-seeking rather than lack of policy success drive programmatic change. This is because the incentives resulting from a (long-lasting) exclusion from government are usually much more unambiguous than a lack of policy success since a lack of success at elections or in the coalition game are directly related to a party’s programmatic position while the reasons for disappointing policy performances can usually be sought elsewhere.
First online: 12 July 2019
Gesehen am 02.03.2021